Financial Decisions, Profitability, and Dividend Policy Impact on Firm Value: Evidence from IDX Quality 30 Companies: Pengaruh Keputusan Keuangan, Profitabilitas, dan Kebijakan Dividen terhadap Nilai Perusahaan: Bukti dari Perusahaan IDX Quality 30. - Linda Novita Ningrum; Detak Prapanca (Universitas Muhammadiyah Sidoarjo, 2024)
This study aims to examine and analyze the influence of Financial Decisions, Profitability, and Dividend Policy on Firm Value in IDX Quality 30 companies listed on the Indonesian Stock Exchange from 2018 to 2020. Employing a quantitative associative approach, the research utilizes a sample of 20 companies comprising 60 financial reports over the specified period. Secondary data is analyzed using panel data analysis techniques. The findings indicate that Financial Decisions and Profitability significantly affect Firm Value in IDX Quality 30 companies during the study period. However, Dividend Policy does not have a significant impact on Firm Value in these companies. Collectively, Financial Decisions, Profitability, and Dividend Policy have a simultaneous influence on Firm Value in IDX Quality 30 companies listed on the Indonesian Stock Exchange from 2018 to 2020. This research underscores the importance of financial decision-making and profitability in enhancing firm value for investors and policymakers.Highlights : Influence of Financial Factors: This study investigates the impact of financial decisions, including capital structure and investment choices, along with profitability metrics on firm value, providing insights into the financial dynamics of IDX Quality 30 companies. Dividend Policy Analysis: The research evaluates the role of dividend policy in shaping firm value, contributing to the understanding of the dividend practices' effectiveness in Indonesian stock market companies. Investor and Policy Implications: The findings offer valuable implications for investors and policymakers, emphasizing the significance of prudent financial management and profitability for enhancing firm value in the Indonesian stock market context. Keywords: Financial Decisions, Profitability, Dividend Policy, Firm Value, Indonesian Stock Exchange